PENINGKATAN PENGETAHUAN GIZI SEIMBANG PADA IBU BALITA MELALUI EDUKASI DAN SIMULASI PEMBUATAN MAKANAN BERGIZI DI DESA KEBUMEN, BATURRADEN - Kusumawardani, Lita Heni; Khoiriyah, Anis; Trenggono, Adinda Handayani; Saputra, Rinda Bagus; Annisa, Selina Nur; Muniroh, Siti Wakhidatun; Kholifa, Eva; Putri, Esa Shofiantyna; Riyanti, Irna; Purnomo, Diki (Journal of Bionursing, 2020)
Introduction: The problem of malnutrition in children under five is still a problem that has not been overcome properly. The role of the family in overcoming the problem of malnutrition is very necessary because toddlers have a dependency in terms of nutritional fulfillment. At present the family's knowledge and awareness of the importance of providing nutrition to infants is still lacking. Therefore, efforts are needed to overcome this problem by increasing the provision of appropriate nuntrisi education for children under five so that toddlers avoid malnutrition. Objective: This study aimed to increase the mother's knowledge about balanced nutrition in infants. Methods: The practice method used education and simulation intervention for 4 weeks. The activity was attended by 22 mothers of children under five by involving health cadres. Results: The results of the study showed that educational and simulation interventions were able to increase the knowledge and skills of mothers of toddlers related to balanced nutrition based on the results of p value = 0.037. Conclusion: Educational intervention and simulation of balanced nutrition could be an opportunity for community nurses to develop promotive and preventive efforts in the prevention of malnutrition, especially stunting in infants.